Monetary policy transparency and pass-through of retail interest rates - Liu, Ming-Hua; Margaritis, Dimitri; Tourani-Rad, Alireza (Journal of Banking & Finance, 2008)
This paper examines the degree of pass-through and adjustment speed of retail interest rates in response to changes in benchmark market rates in New Zealand during the period 1994–2004. We consider the effects of policy transparency and financial structure of the monetary transmission mechanism. New Zealand is the first OECD country to adopt a full-fledged inflation targeting regime with specific accountability and transparency provisions. Policy transparency was further enhanced by a shift from quantity (settlement cash) to price (interest rate) operating targets in 1999. Using Phillips–Loretan estimates of cointegrating regressions we find complete long-term pass-through for some but not all retail rates. Our results also show that the introduction of the Official Cash Rate (OCR) increased the pass-through of floating and deposit rates but not fixed mortgage rates. In line with previous studies we find the immediate pass-through of market interest rates to bank retail rates to be incomplete. Although we find no statistical evidence for asymmetric response of retail rates to changes in market rates other than for business lending rates in the pre OCR period, differences in the magnitude of mean adjustment lags indicate that banks appear to pass on decreases to fixed mortgage rates faster. Overall, our results confirm that monetary policy rate has more influence on short-term interest rates and that increased transparency has lowered instrument volatility and enhanced the efficacy of policy.